2016
DOI: 10.1089/can.2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Human Metabolites of Cannabidiol: A Review on Their Formation, Biological Activity, and Relevance in Therapy

Abstract: Cannabidiol (CBD), the main nonpsychoactive constituent of Cannabis sativa, has shown a wide range of therapeutically promising pharmacological effects either as a sole drug or in combination with other drugs in adjunctive therapy. However, the targets involved in the therapeutic effects of CBD appear to be elusive. Furthermore, scarce information is available on the biological activity of its human metabolites which, when formed in pharmacologically relevant concentration, might contribute to or even account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
204
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(216 citation statements)
references
References 112 publications
4
204
1
Order By: Relevance
“…Cannabielsoin (CBE) is a phytocannabinoid metabolite which can be produced by photo-oxidation from CBD and CBDA [74, 75], or by biotransformation using tissue cultures under normal growth conditions [76, 77]. The ability of this compound to modulate the cannabinoid CB 1 and CB 2 receptors has not been described thus far.…”
Section: Pharmacology Of Selected Phytocannabinoidsmentioning
confidence: 99%
“…Cannabielsoin (CBE) is a phytocannabinoid metabolite which can be produced by photo-oxidation from CBD and CBDA [74, 75], or by biotransformation using tissue cultures under normal growth conditions [76, 77]. The ability of this compound to modulate the cannabinoid CB 1 and CB 2 receptors has not been described thus far.…”
Section: Pharmacology Of Selected Phytocannabinoidsmentioning
confidence: 99%
“…Both agents cause a variety of pharmacological effects but do not have the psychotropic properties which are characteristic for THC. CBD and CBDV are antiepileptic, anticonvulsant, and antipsychotic (Fernández-Ruiz et al 2013; Hill et al 2012; Rosenberg et al 2015; Ujvary and Hanus 2016); furthermore, it was postulated that the former compound prevents inflammation (Borrelli et al 2009) and may act as an anti-carcinogen (Aviello et al 2012; Massi et al 2013). Figure 1a–c depict the structure of the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies using human liver microsomes revealed that 6α‐hydroxylation of CBD is mediated by CYP3A4 and CYP2C19 isoforms, 6β‐hydroxylation is induced by CYP3A4, whereas 7‐hydroxylation is mediated by CYP2C19 . Glucuronosyltransferase and sulfotransferases enzymes are also involved in the metabolism of CBD . At present, more than fifty metabolites from CBD have been identified in urine .…”
Section: Is Cannabidiol a New Hope For Drug‐resistant Epilepsy?mentioning
confidence: 99%
“…The most abundant metabolites are 7‐carboxy‐cannabidiol (7‐COOH‐CBD), 7‐hydroxy‐cannabidiol (7‐OH‐CBD), and 6‐hydroxy‐cannabidiol (6‐OH‐CBD). Although the biological activity of many of CBD metabolites is unknown, preclinical studies suggest that 7‐OH‐CBD obtained from humans induces anticonvulsant effects in mice…”
Section: Is Cannabidiol a New Hope For Drug‐resistant Epilepsy?mentioning
confidence: 99%
See 1 more Smart Citation